ANALISIS KUALITAS SOAL KOGNITIF MATERI SISTEM PERNAPASAN MANUSIA - Khasanah, Uswatun; Fitriyah, Lina Arifah (Discovery : Jurnal Ilmu Pengetahuan, 2023)
Learning evaluation is an important activity to determine the achievement of students' learning abilities in the learning process. Based on observations, it is known that science learning evaluation questions that have been given to students have never been analyzed on an empirical basis. The absence of empirical analysis indicates that there is no process of revising or sorting out valid or invalid questions. Due to this, it is deemed necessary to analyze the quality of cognitive questions. The aim of this research is to describe the quality of cognitive questions regarding the respiratory system in humans. This development uses the ADDIE model. The questions developed were 20 questions which were then validated which included aspects of material, construction, language and appearance. The research results showed that the cognitive questions on the human respiratory system material were declared to meet very good quality with a percentage of 95.24% and could be used in learning evaluation.